Iodine Excess as an Environmental Risk Factor for Autoimmune Thyroid Disease - Luo, Yuqian (MDPI, 2014)
The global effort to prevent iodine deficiency disorders through iodine supplementation, such as universal salt iodization, has achieved impressive progress during the last few decades. However, iodine excess, due to extensive environmental iodine exposure in addition to poor monitoring, is currently a more frequent occurrence than iodine deficiency. Iodine excess is a precipitating environmental factor in the development of autoimmune thyroid disease. Excessive amounts of iodide have been linked to the development of autoimmune thyroiditis in humans and animals, while intrathyroidal depletion of iodine prevents disease in animal strains susceptible to severe thyroiditis. Although the mechanisms by which iodide induces thyroiditis are still unclear, several mechanisms have been proposed: (1) excess iodine induces the production of cytokines and chemokines that can recruit immunocompetent cells to the thyroid; (2) processing excess iodine in thyroid epithelial cells may result in elevated levels of oxidative stress, leading to harmful lipid oxidation and thyroid tissue injuries; and (3) iodine incorporation in the protein chain of thyroglobulin may augment the antigenicity of this molecule. This review will summarize the current knowledge regarding excess iodide as an environmental toxicant and relate it to the development of autoimmune thyroid disease.